Policies to optimize the performance of credit guarantee schemes during financial crises. - Sung, Su Kim; Asian Development Bank (Manila,Philippines Asian Development Bank, [2021])
A CGS must be set up and operated within the existing, and unique, financial environment of a country. Yet, it is among the most successful, easily replicable, and market friendly interventions for excluded borrowers. In this brief, principles to be considered while setting and operationalizing a CGS are provided, focusing on (i) legal and regulatory setup, (ii) corporate governance, (iii) risk management, and (iv) revenue components.
Keywords: Finance -- Developing countries; Small and medium enterprise; Electronic book